Lauso y Eulalia: Transformaciones del tópico de la mors immatura en Peristephanon 3 de Prudencio (Argos, 2025)
This paper examines the evolution of the topic of mors immatura in thePeristephanon 3 by Prudentius, focusing on the relationship between twocharacters: Lausus and Eulalia. This reading proposal is supported by thepresence of certain points of contact between the characters portrayed by Virgiland Prudentius. We argue that intertextuality serves to highlight how theappreciation of their deaths differs between the two authors, and how this contrastreflects two divergent worldviews.
Keywords: Virgil; Prudentius; mors immatura; Lausus; Eulalia; aemulatio